Renal Function Influences Diagnostic Markers in Serum and Urine: A Study of Guanidinoacetate, Creatine, Human Epididymis Protein 4, and Neutrophil Gelatinase–Associated Lipocalin in Children. (15th October 2019) - Salvador, Cathrin L; Tøndel, Camilla; Rowe, Alexander D; Bjerre, Anna; Brun, Atle; Brackman, Damien; Bolstad, Nils; Mørkrid, Lars
Abstract: Background: Impaired renal function may affect the level of diagnostic disease markers. The aim of the study was to investigate the effect of measured glomerular filtration rate (GFR) on 4 diagnostic markers in blood and urine—guanidinoacetate (GAA), creatine (CRE), human epididymis protein 4 (HE4), and neutrophil gelatinase–associated lipocalin (NGAL)—and how this could affect the decision and reference limits. Methods: We examined 96 children (median age 9.2 years, range 0.25–17.5) with different stages of chronic kidney disease (CKD). GFR [median 65.9 mL · min −1 · (1.73 m 2 ) −1, range 6.3–153] was measured by iohexol clearance using 7 venous blood samples after iohexol injection. Fasting serum and urinary GAA, CRE, HE4, NGAL, and creatinine (crn) were analyzed. After appropriate transformation of the markers, a multiple linear regression analysis examined the influence of age, sex, and measured GFR. Results: The level of GFR significantly affected S-GAA ( P = 2 × 10 −4 ) and U-GAA/crn ( P = 5 ×10 −11 ), leading to decreased values in renal impairment. GFR did not correlate significantly with the level of CRE and to a minor degree did the U-CRE/crn ratio ( P = 0.54 and 0.01, respectively). The level of GFR significantly affected S-HE4 ( P = 4 × 10 −31 ) and U-HE4/S-HE4 ratio ( P = 2 × 10 −21 ) with increased serum values and decreased U-HE4/S-HE4 ratio in renal impairment. S-NGAL increased with decreasing kidney function ( P = 2 × 10 −19 ). Conclusions: Diagnostic disease markers may be influenced by the renal function, and this must be taken into account when interpreting test results. Decreased renal function could change the level of the marker above or below decision limits, leading to diagnostic misinterpretation. Clinical Trial Registration: ClinicalTrials.gov, Identifier NCT01092260, https://clinicaltrials.gov/ct2/show/NCT01092260?term=tondel&rank=2